Hemifield coding in ventral object-sensitive areas – Evidence from visual hemiagnosia. (January 2018) - Rennig, Johannes; Karnath, Hans-Otto; Cornelsen, Sonja; Wilhelm, Helmut; Himmelbach, Marc
Abstract: Electrophysiological monkey and human neuroimaging studies have reported a lateralization of signal processing in object perception. However, it is unclear whether these results point to a unique topographically organized signal processing in either hemisphere, or if these results represent a rather negligible spatial organization of otherwise redundant object perception systems in both hemispheres. We tested a group of 10 patients with lesions to ventral object processing regions and spared primary visual functions with lateral presentations of different categories of object stimuli. Object perception in the contralesional visual field was impaired while object perception on the ipsilesional hemifield was intact. These results demonstrate that the object perception system needs two intact ventral pathways for unimpaired object perception across the whole visual field; the loss of one system cannot be fully compensated by its contralateral homolog or spared parts of the lesioned ventral stream.